Experimental analysis on the dynamic response of moored semi-submersible in regular wave / Nik Mohd Khairuddin Nik Ismail and Mohd Azahari Johan - Nik Ismail, Nik Mohd Khairuddin; Johan, Mohd Azahari (2017)
The reaction to the translation motion specifically heave response to the mooring line tension of a typical semi-submersible with square column under regular waves in wave heading condition is reported in this paper. A 112.1 kg model of semisubmersible with geometrically scale 1:81 has been tested in physical wave tank under wave frequency from 0.4297 Hz to 1.7189 Hz with interval 0.1433 Hz. Model was moored horizontally which attached to the structure above the water surface level in head wave with four linear springs at corresponding column respectively. Such a system does not have practical usage but is used to study the loading and response of the semisubmersible in the absence of the catenary mooring lines. The tensions on the mooring lines is measured by load cells coincide with the non-contacting optic tracker. Optic tracker is used to accomplish the measurement of heave response. The force measured by the load cells were analyzed to obtained the behavior of the mooring lines-tens ion at every frequency. From the experimental analysis, it is found that under wave heading condition the tension in forward mooring lines is 2 to 4 times greater than the tension in aft mooring lines. The heave obviously showed that their response directly influenced by the mooring line tension. The mooring forces are not equally shared by forward and aft mooring lines. It also showed that the behavior of all mooring lines forces at each column have a similar trend along the frequency.